Penerapan Cognitif Behavior Therapi (CBT) Pada Ibu Nifas Sebagai Upaya Pencegahan Depresi Post Partum Di Kabupaten Klaten - Murwati Murwati; Suroso Suroso (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Cognitive Behavior Teraphi, Postpartum Depression. Postpartum mothers who are unable to adjust to their new role may experience psychological disorders such as postpartum depression. In Klaten found 36.7% postpartum experienced postpartum depression (Imaninditya, Murwati, 2014). Family support and good health care proved to have an effect on the postpartum depression (Wahyuni, et al, 2014). In addition, cognitive intervention is needed that can overcome the condition of the post-partum mother. This research design is quasi experiment type post test control group design, sample is normal postpartum mother day to 10 - 40, BPM working area of health office of Klaten regency, the sample size is 25 treatment group and 25 control group with Purposive consequtive sampling technique . The act of using CBT(Cognitive Behavior therapy)-based Cognitive Counseling Guidelines and for measuring DPP using EPDS (Edinburg postnatal Depression Scale). The study found 16% depression syndrome in the treatment group and 52% in the control group. The value of p = 0.014, the application of CBT in the postpartum mother can prevent the occurrence of postpartum depression.